Pengaruh Inflasi, Pertumbuh Ekonomi, Jumlah Penduduk Terhadap Kesejahteraan Dengan ZIS Sebagai Variabel Moderasi - Siti Ni'matu Fadhilah; Fany Indriyani; Suharsono Suharsono (Prodi Perbankan Syariah FAI UMT, 2022)
This study was conducted to analyze the Effect of Inflation, Economic Growth, Population on Welfare in Indonesia for the 2015-2019 Period with Zakat, Infaq, Alms (ZIS) as Moderating Variables. This study uses quantitative research using multiple regression analysis with the Moderated Regression Analysis (MRA) test. This study uses secondary data in the form of monthly time series data. Then processed using the tool Eviews 9. This analysis includes Stationarity, Multiple Regression Test, Statistics test (Ttest, Determinant Coefficient (R2) and Classical assumption test.The results of this study are that the inflation variable has a positive and significant effect on welfare in Indonesia for the 2015-2019 period. Economic growth variable has a positive and insignificant effect on welfare in Indonesia for the 2015-2019 period. The population variable has a positive and insignificant effect on welfare in Indonesia for the 2015-2019 period. Simultaneously, inflation, economic growth, population have an effect on welfare in Indonesia for the 2015-2019 period. Zakat, Infaq, Alms (ZIS) can moderate inflation on welfare in Indonesia for the 2015-2019 period. Zakat, Infaq, Alms (ZIS) cannot moderate inflation on welfare in Indonesia for the 2015-2019 period. Zakat,Infaq, Alms (ZIS) can moderate the population towards welfare in Indonesia for the 2015-2019 perid.